STUDYING MEASURES FOR PREVENTION OF COMPLICATIONS OF FACIAL PLASTIC SURGERY - Miraskad Isomov (Innovate Conferences, 2025)
This article discusses the main complications that arise after facial plastic surgery, and also suggests approaches to their assessment and analysis. The use of modern methods of diagnosis and prevention of complications is key to minimizing risks and improving the quality of medical services in the field of plastic surgery. Particular attention is paid to factors influencing the frequency of complications, as well as methods of their prevention and treatment.
Keywords: facial plastic surgery, complications, diagnosis, prevention, rehabilitation, analysis, aesthetic medicine, surgical risks.